Digitalization of Hadith and its Challenges in the Current of Globalization - Arbi Nazhief Fauzan; Endad Musaddad (Konsultan Jurnal Ilmiah Indonesia, 2025)
This research prioritizes the study of hadith that develops in the midst of globalization and advances in digital technology. Hadith, as the source of Islamic teachings after the Qur'an, has undergone a significant transformation along with the ease of obtaining information. Muslims can now study the Prophet's sunnah from digital platforms such as Maktabah Syamilah and Lidwa Pusaka. Digitalization brings many benefits, such as easy access to the whole world, rapid dissemination through social media, moral strengthening, and ease of reference. Digitization of texts, audiovisual content, and visualization of hadith in the form of images or memes are the three main forms of transformation. Apps such as “My Hadith” show innovation in the presentation of complete and modern hadith. Nonetheless, the digital age presents some problems such as the dissemination of information without clear sources. Misinterpretation may occur as authority shifts from scholars to social media figures. As a result, adhering to proper regulations while using technology such as source verification and data protection is essential. The concept of “living hadith” emphasizes the application of hadith principles in this social and cultural context. This method complements textual research by emphasizing daily practice. Verification of sanads, strengthening of hadith science, and caution in handling digital content are all steps that must be taken to combat false hadith. Although digitization offers new opportunities, technology should still be used with caution so that the message of the hadith remains valid and relevant.